UPAYA PREVENTIF GURU KRISTEN DALAM MENGHADAPI DEGRADASI MORAL ANAK - Dwi Novita Sari (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
The current phenomenon of child delinquency leads to moral degradation. Children are no longer victims of violence but also become perpetrators. The emergence of cases of destruction, abuse, rape, and even murder carried out by children, shows the weakness of moral education in Indonesia. Two main factors influence, namely external and internal. There must be synergy between parents, teachers, and the community to educate children. In addition to moral education in the family and society, school becomes a parent's partner in educating and instilling moral values ​​in children in school. In this case, the teacher has a significant role in shaping the child into a moral person. Especially in this case, Christian teachers (Christian teachers) need to be aware of children's needs for moral values because these values ​​align with noble Christian values. This research is here to help Christian teachers by offering steps to teach moral values ​​to children in school. The author used the descriptive method so that readers could see a picture of the research results more closely. The efforts to overcome children's moral degradation in school include creating a moral community, designing shared moral discipline, upholding moral discipline, teaching conflict resolution, and guiding students.